Irish tuberculosis death rates: a statistical study of their reliability, with some socio-economic correlations - Counihan, J.E.; Dillon, T.W.T. (Statistical and Social Inquiry Society of Ireland, 1944)
In an important paper which was published in the Journal of this Society for 1930, Geary surveyed Irish tuberculosis statistics. This communication has as its first aim to analyse along similar lines the figures of the decade 1926-36. Various points which emerged during the discussion on his paper will be examined in some detail, and in particular the validity of Irish tuberculosis statistics is submitted to a close scrutiny.
Read on Friday, 29th October, 1943
Keywords: Tuberculosis; Death rate; Population change; Disease statistics; 314.15